Effects of Formal Education for Patients with Inflammatory Bowel Disease: A Randomized Controlled Trial - Barbara M Waters; Louise Jensen; Richard N Fedorak (Canadian Journal of Gastroenterology)
BACKGROUND: Patients with inflammatory bowel disease (IBD) suffer physical dysfunction and impaired quality of life (QOL), and need frequent health care. They often lack knowledge about their disease and desire more education. Educational interventions for other chronic diseases have demonstrated reduced health care use and increased knowledge, medication adherence and QOL.